2022
DOI: 10.2196/36842
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth and Remote Interventions for Children With Cerebral Palsy: Scoping Review

Abstract: Background Remote treatment, or telehealth, has shown promise for children with cerebral palsy (CP) prior to 2020; however, the beginning of the global COVID-19 pandemic limiting access to hospitals for face-to-face treatments has driven the need for telehealth and led to a surge in its development. Due to the recent developments, there has been limited synthesis of the available evidence of telehealth for children with CP. Objective This study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…21 Chen et al [42] 2021 Pediatric rehabilitation perspective New York N/A N/A It is becoming increasingly important in pediatric rehabilitation to use telemedicine as a safe and effective means of communication, evaluation, and treatment, especially amid the current COVID-19 outbreak. 22 Akulwar-Tajane and Bhatt [43] 2021 Prospective quasiexperimental India 3.02 ± 2.1 21 children Clinical results for children have improved as a result of telerehabilitation. Families expressed a desire for in-person sessions despite their happiness with TR services.…”
Section: Uk Mean Age = 19 Yr 44 Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Chen et al [42] 2021 Pediatric rehabilitation perspective New York N/A N/A It is becoming increasingly important in pediatric rehabilitation to use telemedicine as a safe and effective means of communication, evaluation, and treatment, especially amid the current COVID-19 outbreak. 22 Akulwar-Tajane and Bhatt [43] 2021 Prospective quasiexperimental India 3.02 ± 2.1 21 children Clinical results for children have improved as a result of telerehabilitation. Families expressed a desire for in-person sessions despite their happiness with TR services.…”
Section: Uk Mean Age = 19 Yr 44 Individualsmentioning
confidence: 99%
“…Moreover, this review will contribute to the current evidence base as despite 3 previous reviews having been conducted in this area, 1 was not specific to children with CP, [20] and 1 only focused on therapy for the upper extremities, [21] and 1 review was conducted during COVID-19 which reported studies primarily regarding telerehabilitation before the COVID-19 pandemic occurred. [22] 2. Methodology…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, even in TH and DH, one can currently count on the use of emerging technologies, such as robotics [ 24 , 25 , 26 , 27 ], augmented reality [ 28 ], virtual reality [ 29 ], and artificial intelligence [ 30 , 31 ]. Moreover, assistive technologies have played a strategic role during the pandemic as they were consolidated in the context of different applications and disabilities relating communication and motion [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: The Impact Of Covid-19 In This Fieldmentioning
confidence: 99%
“…Telerehabilitation has several advantages, such as accessibility, time efficiency, and costeffectiveness, for both families and healthcare providers, as the communication between them occurs digitally and remotely [15,16]. There are few well-controlled studies of telerehabilitation for children with CP, most lacking breadth and methodological quality [17]. However, several studies report positive results for the feasibility of telerehabilitation for children with various diagnoses [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Coaching is generally found to be a viable intervention in early intervention studies because the model of parent coaching is strongly aligned with the scope of professional interveners [21] and has commonly also been used in other recent early intervention studies [5,22,23]. Nevertheless, there is a need for further investigations of telerehabilitation, as few studies compare its treatment effects with those of established and evidence-based in-person methods [17][18][19]. The most effective telerehabilitation programs appear to incorporate coaching methods and parental implementation [19].…”
Section: Introductionmentioning
confidence: 99%